Strategi Bisnis Bank Syariah di Masa Pandemi Covid-19 Pada PT. Bank Panin Dubai Syariah Cabang Makassar - Tri Mulato; Asyraf Mustamin; Supriadi Supriadi; St Hafsah Umar; Surya Ningsih (ITB AAS INDONESIA Surakarta, 2021)
The purpose of this study was to determine the development of PT Bank Panin Dubai Syariah during the covid-19 pandemic. And to find out the business strategy implemented by PT Bank Panin Dubai Syariah Makassar Branch during the covid-19 pandemic. The research method used in this research is qualitative by describing the development and business strategy of Panin Dubai Syariah Bank Makassar Branch. This type of research is a field study, primary data collection. Sources of data were obtained directly with interview data collection techniques and documentation from various sources. The data analysis technique used is descriptive qualitative, which describes the development of PT Bank Panin Dubai Syariah during the pandemic. As well as the Business Strategy carried out by PT Bank Panin Dubai Syariah Makassar branch. The results of the research on the growth of PT Bank Panin Dubai Syariah in the period May 2020 to May 2021 experienced an increase in assets of 7.6 percent, and for murabahah financing, it decreased by -44 percent. Current accounts grew by 11 percent, savings grew by 27 percent, and time deposits decreased by -7.9 percent. The business strategy implemented by PT Bank Panin Dubai Syariah during the Covid-19 pandemic was to improve office services by implementing health protocols, increasing digital-based services, increasing ATM, Mobile Banking, and Cash Management System facilities to fulfill customer transactions. For financing recovery for financing affected by COVID-19 so that they can recover, as well as continuing to carry out product offerings and penetration to attract new financing.